An investigation of the convective region of numerically simulated squall lines - Bryan, George Howard (ProQuest Dissertations & Theses, 2003)
High resolution numerical simulations are utilized to investigate the thermodynamic and kinematic structure of the convective region of squall lines. A new numerical modeling system was developed for this purpose. The model incorporates several new and/or recent advances in numerical modeling, including: a mass- and energy-conserving equation set, based on the compressible system of equations; third-order Runge-Kutta time integration, with high (third to sixth) order spatial discretization; and a new method for conserved-variable mixing in saturated environments, utilizing an exact definition for ice-liquid water potential temperature. A benchmark simulation for moist environments was designed to evaluate the new model. It was found that the mass- and energy-conserving equation set was necessary to produce acceptable results, and that traditional equation sets have a cool bias that leads to systematic underprediction of vertical velocity. The model was developed to run on massively-parallel distributed memory computing systems. This allows for simulations with very high resolution. In this study, squall lines were simulated with grid spacing of 125 m over a 300 km x 60 km x 18 km domain. Results show that the 125 m simulations contain sub-cloud-scale turbulent eddies that stretch and distort plumes of high equivalent potential temperature ( e) that rise from the pre-squall-line boundary layer. In contrast, with 1 km grid spacing the high e plumes rise in a laminar manner, and require parameterized subgrid terms to diffuse the high e air. The high resolution output is used to refine the conceptual model of the structure and lifecycle of moist absolutely unstable layers (MAULs). Moist absolute instability forms in the inflow region of the squall line and is subsequently removed by turbulent processes of varying scales. Three general MAUL regimes (MRs) are identified: a laminar MR, characterized by deep (∼2 km) MAULs that extend continuously in both the cross-line and along-line directions; a convective MR, containing deep (∼10 km) cellular pulses and plumes; and a turbulent MR, characterized by numerous moist turbulent eddies that are a few km (or smaller) in scale. The character of the laminar MR is of particular interest. Parcels in this region experience moist absolute instability for 11–17 minutes before beginning to overturn. Conventional theory suggests that overturning would ensue immediately in these conditions. Two explanations are offered to elucidate why this layer persists without overturning. First, it is found that buoyancy forcing (defined as the sum of buoyancy and the vertical pressure gradient due to the buoyancy field) is reduced in the laminar MR as compared to that of an isolated parcel. The geometry of the laminar MR is directly responsible for this reduction in buoyancy forcing; specifically, the MAUL extends continuously in the along-line direction and for 10 km in the cross-line direction, which inhibits the development of vertical motions due to mass continuity considerations. (Abstract shortened by UMI.)